2003
DOI: 10.1177/1087057103255988
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Higher Throughput Microsomal Stability Screening Assay for Profiling Drug Discovery Candidates

Abstract: Metabolic stability plays an important role in the success of drug candidates. First-pass metabolism is one of the major causes of poor oral bioavailability and short half-life. Traditionally, metabolic stability was evaluated at a later stage of drug discovery and required laborious manual manipulations. With the advance of high-throughput screening, combinatorial chemistry, and early profiling of drug-like properties, automated and rapid stability assays are needed to meet the increasing demand of throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 12 publications
3
89
0
1
Order By: Relevance
“…Compounds 7a, 8a, 16a, 19a, 22a, 27a and 27 were tested according to established method [34][35][36] For evaluation of phase I and II metabolic stability 1 µM compound was incubated with 1 mg/ml pooled mammalian liver S9 fraction (BD Gentest), 2 mM NADPH regenerating system, 1 mM UDPGA and 0.1 mM PAPS at 37°C for 0, 5, 15 and 60 minutes at a final volume of 100 µL. The 20 incubation was stopped by precipitation of S9 enzymes with 2 volumes of cold acetonitrile containing internal standard.…”
Section: Biological Methodsmentioning
confidence: 99%
“…Compounds 7a, 8a, 16a, 19a, 22a, 27a and 27 were tested according to established method [34][35][36] For evaluation of phase I and II metabolic stability 1 µM compound was incubated with 1 mg/ml pooled mammalian liver S9 fraction (BD Gentest), 2 mM NADPH regenerating system, 1 mM UDPGA and 0.1 mM PAPS at 37°C for 0, 5, 15 and 60 minutes at a final volume of 100 µL. The 20 incubation was stopped by precipitation of S9 enzymes with 2 volumes of cold acetonitrile containing internal standard.…”
Section: Biological Methodsmentioning
confidence: 99%
“…If the concentrations have not been determined, a range of 1-10 μM of the final drug concentration can generally be used to closely mimic in vivo levels of the drug. However, literature reported that the incubating concentrations of the test drugs (0.5-15 μM) affected the stability results of these drugs in the same microsomal preparation [18]. In general, a test drug at its higher concentration (e.g., 10 μM) shows more stable in the microsomes than at its lower concentration.…”
Section: Metabolism By Microsomesmentioning
confidence: 99%
“…However, it has been shown that the activity of the commercial microsomes varied significantly from batch to batch, and from vendor to vendor. For instance, the rat liver microsomes from two vendors showed great activity in metabolizing drugs buspirone and loperamide, while those from the third vendor exhibited no activity at all; and three different batches of rat liver microsomes from the same vendor resulted in different activity in metabolizing buspirone and loperamide [18]. The differences in the microsomal activity may be due to inherent animal-to-animal variation and differences in preparation processes among the vendors.…”
Section: Metabolism By Microsomesmentioning
confidence: 99%
See 2 more Smart Citations